Phytotoxicity of leaf constituents from bamboo (Shibataea chinensis Nakai) on germination and seedling growth of lettuce and cucumber - Kuang, Y. (2017)
The leaf extracts of bamboo (Shibataea chinensis Nakai) and its fractions (ethyl acetate, n-butanol and water) obtained after extraction with petroleum ether were assayed on seed germination and seedling growth of lettuce and cucumber. The leaf extract showed the lowest phytotoxic activity while the n-butanol fraction was the most bioactive on both target plants. A bioassay guided isolation of the n-butanol fraction led to the isolation of five phytotoxic compounds. The chemical structures of these compounds were elucidated by nuclear magnetic resonance as apigenin (I), quercetin (II), daucosterol (III), 3,3´,4´,5-tetrahydroxy-7-methoxyflavone (IV) and p-methoxybenzoic acid (V). The quercetin, apigenin and daucosterol were more phytotoxic to germination (IC50=7.26-7.95 ppm), root (IC50=2.97-6.33 ppm) and shoot elongation (IC50=4.89-7.74 ppm) of lettuce than glyphosate (IC50>20 ppm). In cucumber, the p-methoxybenzoic acid showed similar phytotoxic activity (IC50=20 ppm, 6.93 ppm, 10.45 ppm, respectively) to glyphosate (IC50=20 ppm, 7.71 ppm, 10.84 pppm, respectively). Our research suggested that the leaves of S. chinensis have potent allelochemicals and their potential as herbicide should be further investigated.